Competitiveness and crisis - the case of the Baltic States economies - Matysek-Jędrych, Anna (Economics and Business Review, 2012)
The article focuses on the relation between economic crisis and competitiveness of the economy. The Baltic States (Estonia, Latvia and Lithuania) experienced the biggest GDP contraction during the global crisis. Since then, identifying and assessing changes in the relative competitiveness as a consequence of the economic downturn has sparked much interest. The selection of competitiveness measuring tools, which provide the basis for analysis, is of key importance to the conclusions formulated. Employing single macroeconomic variables suggests a much stronger influence of the crisis on competitiveness in comparison to the overall measures (Global Competitiveness Index or IMD Index). However, it is likely that the influence of recession on competitiveness - though certainly present and quite strong - was too short-lived to considerably affect the measures of competitiveness, which were constructed mainly on the basis of the perceptions and opinions of various social and business groups. The main channel through which the crisis undermined competitiveness was macroeconomic situation. It may be generally concluded that a short-term crisis, even if severe, does not have a negative influence on economic competitiveness as long as proper anti-crisis policy is implemented. (original abstract)